KEKUATAN HUKUM AKTA JUAL BELI ATAS PENJUALAN HARTA BERSAMA YANG TANPA PERSETUJUAN SALAH SATU PIHAK DARI MANTAN SUAMI ATAU MANTAN ISTRI (Studi Putusan Nomor 3200/Pdt.G/2016/PA.Lmj.) - Andik Wicaksono (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2020)
Joint property is property acquired during the marriage (article 35 paragraph (1) of law number 1 Year 1974), the acquisition of such property involves the role as well as husband and wife, both roles as well as directly or indirectly. When one party ex-husband or ex-wife sell along the treasure without the consent and knowledge of the ex-husband or ex-wife then the sale is not valid and does not have the force of law (Religious Court ruling of Lumajang Number 3200/Pdt.G/2016/PA. Lmj.). TER Haar says.